STRENGTHENING VILLAGE GOVERNANCE TO SUPPORT COMMUNITY FOOD SECURITY IN GAMPONG LAMTEUBA ACEH BESAR REGENCY: PENGUATAN TATA KELOLA DESA DALAM MENDUKUNG KETAHANAN PANGAN MASYARAKAT DI GAMPONG LAMTEUBA KABUPATEN ACEH BESAR - Novi Mailidarni Novi; Sulaiman; Nyak Yusfa Afrina; Tasliati Djafar; Sayafei Ibrahim; Badruzzaman (PT. ROCE WISDOM ACEH, 2026)
Village food security is a crucial pillar of sustainable rural development, particularly in remote areas with abundant natural resources that have not been optimally managed. Gampong Lamteuba, Aceh Besar Regency, is a rural village characterised by fertile agricultural land and a community largely dependent on staple crop farming for their livelihood. However, one of the main challenges lies in the limited capacity of village governance to coordinate local potential in supporting sustainable food security. This Community Service Program (PKM) aims to strengthen village governance through a participatory approach to enhance community food security. The methods employed include socialisation activities, focus group discussions (FGDs), training sessions, and mentoring for village officials and farmer groups. The results indicate an increased understanding among village authorities and community members regarding the importance of governance in food security, improved coordination between village government and farmer groups, and the formulation of village-level policy recommendations to support local food management. This program contributes to strengthening village governance and community participation in achieving locally based food security.